Manual Handling as Contributor of Low Back Pain for Workers: A Case Study at PT Sumber Mandiri Jaya, Kabupaten Merauke - Sambeko, Boyke Elyas Michael; Susanto, Nugroho; Alfanan, Azir (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Manual handling activities are a main causative factor of low back pain injuries. Around 1.71 billion people worldwide live with musculoskeletal conditions, including low back pain. In the Southeast Asia region, it is estimated that around 369 million people experience low back pain. In Indonesia more than 11.9% of health workers are diagnosed with musculoskeletal disease and diagnostic specific for worker obtained 24.7%. The purpose of this study was to determine the dominant indicators of manual handling for low back pain. Method: Study design used is cross-sectional study. Sample was 62 subjects. The variables of low back pain were collected using a modified questionnaire adopted from the Oswestry Low Back Pain Disability Questionnaire. Data were analyzed with linear regression test for the main indicators contributing to low back pain. Result: Average age of workers is 26.06±7.28, education level senior high school 45%, under 4 years length of work 83.9%. Average manual handling variable is 613.45 ± 383.39, low back pain 6.48 ± 3.607. Manual handling is not significantly related to low back pain r = -0.182. Duration, frequency and load are significant in predicting low back pain. The factors of duration, frequency and lift were estimated to contribute 5.4% for low back pain. Conclusion: The main factors related to low back pain are lifting load for workers, while the factors of lifting duration and frequency are not significantly related to low back pain. The lifting load is the main factor contributing to low back pain.